The Effect of Dissolved Oxygen Distribution on Ammonium Nitrogen Removal in a Pilot-Scale of Vertical Upward-Flow of Aerated Electric Arc Furnace Slag Filter Systems At Various Hydraulic Loading Rates - Mohamed, Wan-Afnizan Wan-; Hamdan, Rafidah; Othman, Norzila; Razi, Mohd-Adib Mohammad-; Zin, Nur-Shaylinda Mohd-; Arshad, Nur-Ain-Nazirah Mohd- (International Journal of Engineering and Technology, 2018)
The performance of an aerated vertical upward-flow electric arc furnace slag filter (VFEAFS) system in treating domestic wastewater was examined in a warm-climate country temperature. Two pilot scale column experiments were conducted at high (2.72 m3/m3.day) and low (1.04 m3/m3.day) hydraulic loading rate (HLR) set-up and the effect of different hydraulic loading levels on pollutant removal efficiency were studied. Aeration was introduced in the filter system at 10 L/min to observe oxygen distribution concentration towards ammonium nitrogen removal. The results demonstrated that both HLR set-up were capable to achieve more than 90% ammonium nitrogen (AN) removal; however, in terms of individual efficiency of the filter system, the VFEAFS of lower HLR performed better in comparison to the higher HLR set-up. The average effluent concentration of AN by both systems were found far below standard A of Malaysian sewage discharge limit (10 mg NH4-N/L). The results achieved in this pilot scale study indicate that removal of ammonium nitrogen in the aerated VFEAFS was explained by nitrification process, and this treatment system could be implemented to the other industry-environmental, municipal or residential wastewater.